The Study Of Influence Of Human Resource Management (HRM) On Implementation Of Clinical Governance In Tehran University Of Medical Sciences Hospitals - Fatemeh Ghazanfari; Hossein Mobaraki (Tehran University of Medical Sciences, 2014)
Background and Aim: Clinical governance is the application of mechanisms at the right time and place to do tasks for patients properly and obtain maximum clinical results. The implementation of clinical governance definitely requires the skills and inclinations of those working in healthcare sector. The main objective of this study is to identify the relationship between human resource management (HRM) on the one hand and the implementation of clinical governance and the optimal establishment of its framework on the other hand through offering strategies for effective human resource management. Materials and Methods: This is a descriptive analytical study conducted in a cross-sectional way in 2012. The sampling method was a two-step cluster sampling. Shariati, Imam Khomeini, and Hashemi Nejad were randomly selected from among the hospitals of Tehran University of Medical Sciences (TUMS). The data collection instrument was a researcher-made questionnaire and a checklist. In each hospital, 30 questionnaires were randomly distributed. The gathered data were analyzed by SPSS. Results: The minimum and maximum scores of clinical governance pertained to Imam Khomeini (594) and Hashemi Nejad (753) hospitals, respectively. Moreover, significant relationships were found between variables of training, recruitment and employment, salaries and benefits on the one hand and clinical governance on the other. Conclusion : Considering the significant relationship between HRM and the implementation of clinical governance, investment in this aspct of clinical governance as the one that influences success in other aspects can be effective in the establishment of clinical governance.